Feels like the real thing: imagery is both more realistic and emotional than verbal thought. - Mathews, A; Ridgeway, V; Holmes, E (2013)
The production of mental images involves processes that overlap with perception and the extent of this overlap may contribute to reality monitoring errors (i.e., images misremembered as actual events). We hypothesised that mental images would be more confused with having actually seen a pictured object than would alternative representations, such as verbal descriptions. We also investigated whether affective reactions to images were greater than to verbal descriptions, and whether emotionality was associated with more or less reality monitoring confusion. In two experiments signal detection analysis revealed that mental images were more likely to be confused with viewed pictures than were verbal descriptions. There was a general response bias to endorse all emotionally negative items, but accuracy of discrimination between imagery and viewed pictures was not significantly influenced by emotional valence. In a third experiment we found that accuracy of reality monitoring depended on encoding: images were more accurately discriminated from viewed pictures when rated for affect than for size. We conclude that mental images are both more emotionally arousing and more likely to be confused with real events than are verbal descriptions, although source accuracy for images varies according to how they are encoded.